A Novel Low Power RF to DC Converter for Wireless Sensor Network - Roy, Kousik; Goswami, Chiranjib; Hasan, Naimul; Priya, Rashmi; Chakraborty, Saswata (International Journal of Computer Sciences and Engineering, 2025)
In this paper the schematic diagrams for realization of low power RF to DC Converter have been illustrated. Here we have implemented the rectifier circuit at 2.45 GHz . -5 dBm,0 dBm,10 dBm input power are taken for the design and simulation of the rectifier circuit. Variation of input power with respect to DC voltage is shown at 2.45 GHz frequency. Likewise change of S1,1 & variation of output power with respect to frequency is also presented. In this paper we have illustrated the schematic design of the rectifier circuit along with the matching circuit utilizing HSMS 2820. Simulations explain that the DC voltage of 0.459V, 0.859V, 3.120V can be obtained at -5dBm, 0dBm, 10 dBm input power when input frequency 2.45GHz and load resistance of 20kΩ.